Perinatal complications of monochorionic diamniotic twin gestations with discordant crown–rump length determined at mid‐first trimester. Issue 2 (7th October 2013) - Nakayama, Soichiro; Ishii, Keisuke; Kawaguchi, Haruna; Yamamoto, Ryo; Murata, Masaharu; Hayashi, Shusaku; Mitsuda, Nobuaki
Abstract Aim The aim of this study was to investigate the value of discordance of crown–rump length (DCRL) at mid‐first trimester to predict adverse outcomes in monochorionic diamniotic twin gestations (MD). Material and Methods This was a retrospective cohort study of the perinatal outcome in MD pregnancies managed from the first trimester onward. DCRL was evaluated between 8 and 10 weeks of gestation. The association between DCRL and perinatal complications, including fetal death, twin–twin transfusion syndrome, severe discordant birthweight (DB), and twin anemia‐polycythemia sequence, was assessed. Results Among 126 cases, a single fetal demise occurred in two (2%) and demise of both fetuses occurred in eight (6%). Five pregnancies (4%) were complicated with twin–twin transfusion syndrome; one case (1%) was twin anemia‐polycythemia sequence and 13 (10%) were DB. Neonatal death occurred in one pair. At 28 days of age, in 115 cases (91%) both twins were alive. In 117 cases (93%), at least one twin survived until 28 days of age. DCRL >12.0% was not related to any perinatal complications but DB (P < 0.01; relative risk: 1.40; 95% confidence interval: 1.06–1.84). Conclusions DCRL in MD during the mid‐first trimester might be useful for predicting DB.